Otolith Biometry - Total Length Relationships in the Population of Hazar Bleak, Alburnus heckeli (Battalgil, 1943) Inhabiting Lake Hazar, Elazig, Turkey - Basusta, Asiye; Bal, Hatice; Aslan, Ergun (Zoological Soc Pakistan, 2013)
In this study, the relationships between Eolith biometry-total fish length of 110 Hazar bleak, Alburnus heckeli (Battalgil, 1943) (Cyprinidae) specimens from Lake Hazar were examined. Total length and weight of specimens ranged between 8.8 and 110 cm and between 4.4 and 13.80 g, respectively. The length, breadth and weight of otoliths of each specimen were measured which were respectively 1.48-2.86 mm, 1.02-2.43 mm and 0.0005-0.002 g. There was strong relationship between the otolith length and total length of fish.
Keywords: Alburnus heckeli; Hazar Bleak; otolith biometry